Which expression is equivalent to 2(2x + 7)
5 answers
4x + 14
Which expression is equivalent to -
-1/5 (10x + 15) - 2?
A -2x – 1 -2 x – 1
B -2x – 4-2 x – 4
C -2x – 3-2 x – 3
D -2x – 5
-1/5 (10x + 15) - 2?
A -2x – 1 -2 x – 1
B -2x – 4-2 x – 4
C -2x – 3-2 x – 3
D -2x – 5
The expression -1/5 (10x + 15) - 2 can be simplified as follows:
-1/5 (10x + 15) - 2 = (-1/5)(10x) + (-1/5)(15) - 2 = -2x - 3 - 2
Therefore, the expression is equivalent to -2x - 5.
The correct answer is D.
-1/5 (10x + 15) - 2 = (-1/5)(10x) + (-1/5)(15) - 2 = -2x - 3 - 2
Therefore, the expression is equivalent to -2x - 5.
The correct answer is D.
Which expression is equivalent to 2/3 (4x - 9)?
A
8x - 18
______
3
B. 8x - 9
____
3
C. 8/3 (x + 18)
D.8/3 (x - 12)
A
8x - 18
______
3
B. 8x - 9
____
3
C. 8/3 (x + 18)
D.8/3 (x - 12)
The expression 2/3 (4x - 9) can be simplified as follows:
2/3 (4x - 9) = (2/3)(4x) + (2/3)(-9) = 8/3x - 6
Therefore, the equivalent expression is 8/3x - 6.
The correct answer is:
D. 8/3 (x - 12)
2/3 (4x - 9) = (2/3)(4x) + (2/3)(-9) = 8/3x - 6
Therefore, the equivalent expression is 8/3x - 6.
The correct answer is:
D. 8/3 (x - 12)